2010
DOI: 10.1063/1.3457862
|View full text |Cite
|
Sign up to set email alerts
|

Growth, electrical rectification, and gate control in axial in situ doped p-n junction germanium nanowires

Abstract: We report on vapor-liquid-solid growth and electrical properties of axial in situ doped p-n junction Ge sub-100 nm diameter nanowires. Room temperature four-point measurements show current rectification of two to three orders of magnitude depending on nanowire doping and diameter. We observe strong backgate control of reverse-bias current of up to three orders of magnitude and explain it by band-to-band tunneling modulated by the backgate-controlled electric field, as confirmed qualitatively via a quasi-three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…In fact, we typically observed linear I–V characteristics from the segments close to the ends of the nanowires (away from p–n junctions). By measuring the gate responses of the non‐rectifying segments,14 we identified the doping types (either p or n) of individual segments13, 15 (see Supporting Information). This electrical characterization, along with the correlated spatial behavior, strongly confirms that the current rectification originates from the intrinsic p–n junction properties of the nanowires…”
mentioning
confidence: 99%
“…In fact, we typically observed linear I–V characteristics from the segments close to the ends of the nanowires (away from p–n junctions). By measuring the gate responses of the non‐rectifying segments,14 we identified the doping types (either p or n) of individual segments13, 15 (see Supporting Information). This electrical characterization, along with the correlated spatial behavior, strongly confirms that the current rectification originates from the intrinsic p–n junction properties of the nanowires…”
mentioning
confidence: 99%
“…Nanowires (NWs) with built‐in p–n junctions along the axial direction have been obtained by Tutuc et al 1 via the growth of an n‐type Ge NW followed by an intrinsic segment after which a p‐type shell was grown all around the intrinsic and n‐type segments. Similar axial p–n junctions in Ge NWs were grown by Son et al 2 while tandem p–n junction NWs have been demonstrated by Kempa et al 3. On the other hand core–shell p–i–n junction Si NWs have been grown by Tian et al 4 which involves extra processing for the fabrication of separate contacts to the n‐ and p‐type segments.…”
Section: Introductionmentioning
confidence: 71%
“…Although alloys may have formed at the device interface, SEM-EDX elemental mapping of the devices confirmed that there was no detectable metal diffusion from the contacts into the semiconductor channel during fabrication (Figure S27). 73…”
Section: Resultsmentioning
confidence: 99%